Nanotechnology diffusion strategy: interdisciplinary teaching to primary school teachers - Camacho-Elizondo, Melissa (2022)
The objective of the research was to disseminate nanotechnology concepts, applications, and benefits among educators from different Costa Rican provinces to increase their acceptance and dissemination of the subject to elementary students. Teachers from different areas of the country were called to participate.  Five training workshops were held in Turrialba, Cahuita, Alajuela, Buenos Aires, and Nicoya covering fundamental nanotechnology concepts and applications, as well as the contributions offered from an educational point of view. The workshops were held in person two full days including talks, practical activities, and discussions. In addition, educational materials were prepared, such as a poster and an information brochure, and two educational videos on nanotechnology. A total of 98 teachers, 87% men and 13% women, from different provinces were trained. Workshop evaluations were positive in terms of the knowledge acquired with an average of 57.30%, compared to 5.10% before starting the training. This project contributed to strengthen teachers’ knowledge about nanotechnology and its applications. In addition, national and international nanotechnology research projects were made known. The above will help teachers disseminate new knowledge to the student population, thus becoming knowledge multipliers.